The Discursive Construction of ‘Good Parenting’ by Romanian Parenting Influencers - Florența Toader (Romanian Journal of Communications and Public Relations, 2023)
This article analyzes promotional and educational content published online by newly emerged parenting influencers in Romania to endorse parenting education programs, workshops, seminars, or books. The paper aims to investigate how these programs construct ‘good parenting’ practices at a discursive level, what (de)legitimation strategies they use to promote products or services, and how they shape power relations between experts and parents. The study uses a multidimensional thematic, critical, and pragmatic discourse analysis approach. The results show that, through discursive strategies, influencers portray ‘good parenting’ as an anxiety and value-driven process. This approach is rooted in a parental determinist view that emphasizes the influence of parental actions on children’s health and well-being. On the other hand, parenting expert influencers depict the ‘good parent’ as a ‘conscious parent’ (a parent that is both child-conscious, and attentive to their own needs and emotions) who should reform old parenting practices to ensure a secure relationship with their children and correct old parenting mistakes. The paper contributes to the growing body of knowledge on the changing nature of parental culture in post-industrial countries, with a particular focus on Romania.